Angiotensin II modulates the murine hematopoietic stem cell and progenitors cocultured with stromal S17 cells. (25th March 2021) - Costa, Maíra M.; Stilhano, Roberta S.; Oliveira, Carlos R.; Barbosa, Chistiano M. V.; Pereira, Gustavo J. S.; Paredes‐Gamero, Edgar J.; Nakaie, Clovis R.; Smaili, Soraya S.; Bincoletto, Claudia
Abstract: Although the existence of the renin–angiotensin system (RAS) in the bone marrow is clear, the exact role of this system in hematopoiesis has not yet been fully characterized. Here the direct role of angiotensin II (AngII) in hematopoietic stem cells (HSCs), common myeloid progenitors (CMPs), granulocyte/monocyte progenitors (GMPs), and megakaryocytes/erythroid progenitors (MEPs), using a system of coculture with stromal S17 cells. Flow cytometry analysis showed that AngII increases the percentage of HSC and GMP, while reducing CMP with no effect on MEP. According to these data, AngII increased the total number of mature Gr‐1 + /Mac‐1 + cells without changes in Terr119 + cells. AngII does not induce cell death in the population of LSK cells. In these populations, treatment with AngII decreases the expression of Ki67 + protein with no changes in the Notch1 expression, suggesting a role for AngII on the quiescence of immature cells. In addition, exposure to AngII from murine bone marrow cells increased the number of CFU‐GM and BFU‐E in a clonogenic assay. In conclusion, our data showed that AngII is involved in the regulation of hematopoiesis with a special role in HSC, suggesting that AngII should be evaluated in coculture systems, especially in cases that require the expansion of these cells in vitro, still a significant challenge for therapeutic applications in humans.